The Effect of Polishing Techniques on Color Change of Nanofill Composite Resin Immersed in Green Tea (Camellia sinensis) - Claudia Nathania Batihalim; Dina Ratnasari (Indonesian Dental Association, 2021)
Introduction: Nanofill composite resin with its filler particle 0.005-0.1 Âµm can have better polishing result so that as a restoration it is more resistant towards staining that is susceptible to occur by the exposure to food and beverage. Polishing is done to improve the color stability of composite resin. Polishing techniques can be divided into one-step technique and multi-step technique. One of the staining agents, green tea tannin can cause discoloration in composite restoration. Objective: This research determine the effect of polishing techniques on the color change of nanofill composite resin after green tea immersion. Methods: The sample used was nanofill composite resin with the diameter of 10 mm and thickness of 2 mm. Samples were divided into 2 groups, 10 samples with one-step polishing technique and 10 samples with multi-step polishing technique. Samples were soaked in distilled water for 24 hours at 37oC and initial color measurements were taken. The treatment was given by immersing the samples in green tea solution for 5x24 hours at 37Â°C incubator. Measurements of the samples final color after the treatment were done after the fifth day. Results: One-step and multi-step polishing techniques affect the overall color value of the nanofill composite resin after treatment. The multi-step technique group had lower overall color value than the one-step technique (p=0.00). There were significant differences in the L, C, and H values after treatment with one-step and multi-step groups (p<0.05). Conclusion: The multi-step polishing technique produced better roughness reduction with the result that less color change.